Nursing Fundamentals - Ernstmeyer, Kimberly; Christman, Elizabeth (Open textbook library., 2020)
This Nursing Fundamentals textbook is an open educational resource with CC-BY licensing developed for entry-level nursing students. Content is based on the Wisconsin Technical College System (WTCS) statewide nursing curriculum for the Nursing Fundamentals course (543-101), the 2019 NCLEX-RN Test Plan, the 2020 NCLEX-PN Test Plan, and the Wisconsin Nurse Practice Act. This book introduces the entry-level nursing student to the scope of nursing practice, various communication techniques, and caring for diverse patients. The nursing process is used as a framework for providing patient care based on the following nursing concepts: safety, oxygenation, comfort, spiritual well-being, grief and loss, sleep and rest, mobility, nutrition, fluid and electrolyte imbalance, and elimination. Care for patients with integumentary disorders and cognitive or sensory impairments is also discussed. Learning activities have been incorporated into each chapter to encourage students to use critical thinking while applying content to patient care situations.